Risks While Deinstitutionalizing Long-Term Elderly Care: The Case of Latvia - Rezgale-Straidoma, Endija; Rasnača, Līga (Socialiniai tyrimai, 2015)
The study deals with the deinstitutionalization of long-term care for elderly people in Latvia. The aim of this study is to identify the risks that elderly people, discharged from long-term care institutions, are likely to face. The research method of this case study is document analysis and a semi-structured interview. The research shows that some mismatch between the declared political aims and the current situation which was clarified through interviews exists. The identified risks have been grouped, analysed, conclusions drawn are provided in the paper.